2000
DOI: 10.1128/aem.66.1.73-79.2000
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Physiological Characteristics of Hyperthermophiles in the Kubiki Oil Reservoir in Niigata, Japan

Abstract: The distribution of culturable hyperthermophiles was studied in relation to environmental conditions in the Kubiki oil reservoir in Japan, where the temperature was between 50 and 58°C. Dominant hyperthermophilic cocci and rods were isolated and shown to belong to the genera Thermococcus and Thermotoga, respectively, by 16S rDNA analyses. Using the most-probable-number method, we found that hyperthermophilic cocci were widely distributed in several unconnected fault blocks in the Kubiki oil reservoir. In 1996 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 51 publications
0
67
0
Order By: Relevance
“…Physiologically, strain TMO T differs from the species Thermotoga hypogea (Fardeau et al, 1997), Thermotoga maritima (Huber et al, 1986), Thermotoga neapolitana (Jannasch et al, 1988), Thermotoga thermarum (Windberger et al, 1989), Thermotoga petrophila and Thermotoga naphtophila (Takahata et al, 2001) by its lower optimal temperature, from the species Thermotoga maritima and Thermotoga neapolitana by its lower salinity range, but from the species Thermotoga hypogea and Thermotoga thermarum by its higher salinity range. Its physiological properties (temperature, pH optima and salinity requirement) are more similar to those of Thermotoga elfii and Thermotoga subterranea.…”
Section: Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologically, strain TMO T differs from the species Thermotoga hypogea (Fardeau et al, 1997), Thermotoga maritima (Huber et al, 1986), Thermotoga neapolitana (Jannasch et al, 1988), Thermotoga thermarum (Windberger et al, 1989), Thermotoga petrophila and Thermotoga naphtophila (Takahata et al, 2001) by its lower optimal temperature, from the species Thermotoga maritima and Thermotoga neapolitana by its lower salinity range, but from the species Thermotoga hypogea and Thermotoga thermarum by its higher salinity range. Its physiological properties (temperature, pH optima and salinity requirement) are more similar to those of Thermotoga elfii and Thermotoga subterranea.…”
Section: Growth Conditionsmentioning
confidence: 99%
“…Until now, representatives of the genus Thermotoga have not been isolated from a thermophilic anaerobic bioreactor (Huber et al, 1986 ;Jannasch et al, 1988 ;Windberger et al, 1989 ;Jeanthon et al, 1995 ;Ravot et al, 1995 ;Fardeau et al, 1997 ;Takahata et al, 2001). Furthermore, Thermotoga species were described as carbohydrate-fermenters that are able to utilize thiosulfate as an electron acceptor (Ravot et al, 1995).…”
Section: Growth Conditionsmentioning
confidence: 99%
“…Recent investigations on an iron-reducing microbial population in the EPR deep-sea hydrothermal vent environment suggested the abundant occurrence of a thermophilic iron-reducing microbial population, predominantly represented by members of Thermococcus and Deferribacter, in relatively oxidative microhabitats (Slobodkin et al, 2001). A body of evidence has demonstrated that sulfidogenic, thermophilic bacteria and archaea, mainly consisting of sulfur-reducing members of Thermotogales and Thermococcales, are predominantly present in global subsurface oil-reservoir environments other than marine hydrothermal systems (L'Haridon et al, 1995;Orphan et al, 2000;Slobodkin et al, 1999;Stetter et al, 1993;Takahata et al, 2000). In addition to members of Thermotogales and Thermococcales, sulfur-reducing and/or metal-reducing members of Deferribacter such as D. desulfuricans SSM1 T and D. thermophilus BMA T may be widely distributed in global deep-sea hydrothermal systems and subsurface oil-reservoir environments and may represent significant microbial components.…”
Section: Comparison With Related Speciesmentioning
confidence: 99%
“…The subsurface biosphere is spatially expansive and contains a vast diversity of potential microbial habitats, including many that approach the known limits of life. Populations of micro-organisms have been found in a variety of subsurface environments including hot formation water associated with deep oil reservoirs L'Haridon et al, 1995 ;Orphan et al, 2000 ;Ravot et al, 1995 ;Slobodkin et al, 1999 ;Stetter et al, 1993 ;Takahata et al, 2000), extremely oligotrophic ground waters in deep crystalline rocks (Stevens & McKinley, 1995), inside ancient subterranean salt K. Takai and others deposits (Grant et al, 1998) and the 250 mC water of a deep geothermal water pool (Takai & Horikoshi, 1999b). In spite of the interest in these findings, many of these microbial habitats remain poorly characterized, mainly due to the difficulties associated with access and sampling.…”
Section: Introductionmentioning
confidence: 99%